Careers guidance in context - Gothard, W. P. (London ; Thousand Oaks, Calif. : SAGE, 2001)
Helping others to make occupational choices requires a combination of skill and a deep understanding of the world of work as it is today and as it will be in the future. Unlike texts which focus only on skill, Careers Guidance in Context is designed to develop understanding of the social, economic and political factors which shape both the labour market and careers guidance as an occupation in itself.
Cover; Contents; Chapter 1 -- Careers Guidance in a New Era; Chapter 2 -- Career Development Theory; Chapter 3 -- Working with Individuals; Chapter 4 -- Group Work: Guidance in a Group Setting; Chapter 5 -- The Discourse of the Labour Market; Chapter 6 -- Careers Education; Chapter 7 -- Anti-oppressive Practice; Chapter 8 -- The Future of Careers Guidance; References; Index.
Includes bibliographical references ([p. 139]-150) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Vocational guidance; Occupations; Professions; occupations (livelihoods); BUSINESS & ECONOMICS -- Careers -- General; Occupations; Vocational guidance; Berufsberatung; Groḃritannien